PENGARUH PENGGUNAAN MODUL TERINTEGRASI NILAI-NILAI KARAKTER DALAM MODEL PEMBELAJARAN SIKLUS 5E TERHADAP KOMPETENSI FISIKA SISWA KELAS XI SMAN 7 PADANG - Yulia Rahmatika (PILLAR OF PHYSICS EDUCATION, 2014)
The achievement of students competences (the integration between assessment’s aspect and characteristic) have not indicated the optimal result because there is no teaching material that integrates between the values of character and learning model. One way to overcome the problem is by making a teaching material as a module by using 5E cycle learning model. The purpose of this research is to know the influence of use an integrated module of character values in 5E cycle learning model toward physical competences students of the XI grade. The design of this research is quasi experimental research. The research uses randomized control group only design. The population of the research is grade XI IPA students of SMAN 7 Padang. In this research, the reseacher choose two classes to be given treatment. The research used purposive sampling technique so that it has been choosen XI IPA 5 as experimental class and XI IPA 4 as control class that each class consists of 40 students. In getting the cognitive aspect, the researcher does a test. Meanwhile, non test technique is done to get affective and psychomotor aspect. The data analysis is done by using t-test with significance level 0,05. Based on the result of the data analysis, it can be concluded that students competence in experimental class is higher than control class for three aspects of assessment. It can be said that the use of an integrated module of character values in 5E cycle learning model gives significant effect toward grade XI student of SMAN 7 Padang.